Emergency and persistence of Escherichia coli ST131 as community-onset antimicrobial resistant urinary tract infection in Rio de Janeiro, Brazil - Eduardo Moreira de Castro; Isadora Silva Barcellos; Guilherme Santoro-Lopes; Ana Paula de Souza da Silva; Luís Guilherme de Araújo Longo; Mariana Anjo Barbosa; Gabriela Camarano de Oliveira; Lucas Cecílio Vilar; Adriana Lúcia Pires Ferreira; Karla Rodrigues Miranda; Beatriz Meurer Moreira (Brazilian Journal of Infectious Diseases)
Urinary Tract Infections (UTI) are among the most common public health problems worldwide, mostly caused by Escherichia coli. High-risk pandemic clones, especially ST131, are known for their association with multidrug resistance. A better understanding of epidemiologic and molecular characteristics may provide insights into the dissemination and evolution of this pathogen. The present study aims to investigate selected clonal characteristics of a large collection of UTI-causing E. coli isolates from Rio de Janeiro, an urban center in Brazil. We set up a collection of 992 E. coli isolates from patients with UTI in 2019. We determined antimicrobial susceptibility, Extended Spectrum Betalactamase (ESBL) production and clonal composition of isolates and compared results with data from 2015. Frequencies of four most isolated pandemic clones (ST131, ST69, ST73 and ST95) were determined by PCR; ST131 clades were determined by PCR and fimH gene sequence; ESBL-producing isolates underwent MLST. Resistance frequencies were > 30 % for ampicillin and ciprofloxacin. ST131 isolates were the most frequent clone (14 %), increasing significantly from 2015, comprising 52 % of all ESBL-producing strains. Clade C formed most ST131 isolates (56 %), including 40 % of all ESBL-producing isolates, most in Clade C2; almost all fimH30. ST131, formed by heterogeneous lineages, was established as a major source of ESBL isolates in the community, with a major contribution to antimicrobial resistant UTI.